Analisis Kestabilan Lereng Tambang Kuari Batu Trass di PT. Indocement Tunggal Prakarsa Desa Kedongdong Kidul Kecamatan Dukupuntang Kabupaten Cirebon Provinsi Jawa Barat - Muhammad Afif Zahrandika; Yuliadi; Noor Fauzi Isniarno (UNISBA Press, 2023)
Abstract. Slope stability is an important factor in planning an open pit mine. A stable slope design will have a major impact on mine economics and production. This study aims to determine the stability of the slopes in the research location area and provide recommendations for optimal mine slope geometry based on the values of the Safety Factor (SF), Probability of Failure (PoF), and Strength Reduction Factor (SRF). Analysis activities were carried out using 2 methods, namely the limit equilibrium method accompanied by probabilistic analysis to determine the PoF value of the mine slope and using the finite element method. Based on the research results, it is known that the constituent rocks on the slopes of the Kedongdong quarry mine are trass stones. On a single slope the recommended mine slope geometry is H= 5 m and Ꝋ= 50o, H= 6 m and Ꝋ= 45o, H= 8 m and Ꝋ= 40o, H= 10 m and Ꝋ= 35o. On the actual overall slope an analysis of 2 sections was carried out, namely section A-A' and section E-E